2016
DOI: 10.3846/16484142.2016.1144221
|View full text |Cite
|
Sign up to set email alerts
|

Formulating alcohol-influenced driver’s injury severities in intersection-related crashes

Abstract: Abstract. Approximately one third of all traffic fatal crashes are alcohol-related in the US according to the National Highway Traffic Safety Administration (NHTSA), alcohol-related crashes cost more than $37 billion annually. Considerable research efforts are needed to understand better significant causal factors for alcohol-related crash risks and driver's injury severities in order to develop effective countermeasures and proper policies for system-wide traffic safety performance improvements. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Also, Papalimperi et al (2019) reported that fatal alcohol-related traffic accidents are more likely to happen during weekends and the summer period than during weekdays. Wu and Zhang (2018) demonstrated that the risk of having severe injuries is higher for alcohol-impaired drivers when the drivers are 65 years old or older and when the drivers make left turns in intersections. Valen et al (2019) reported that at least one of the risk factors speeding, non-use of a seatbelt/helmet, and driving without a valid license were present among most of the drug/alcohol-impaired drivers fatally injured.…”
Section: Trends In Alcohol-related Accidentsmentioning
confidence: 99%
“…Also, Papalimperi et al (2019) reported that fatal alcohol-related traffic accidents are more likely to happen during weekends and the summer period than during weekdays. Wu and Zhang (2018) demonstrated that the risk of having severe injuries is higher for alcohol-impaired drivers when the drivers are 65 years old or older and when the drivers make left turns in intersections. Valen et al (2019) reported that at least one of the risk factors speeding, non-use of a seatbelt/helmet, and driving without a valid license were present among most of the drug/alcohol-impaired drivers fatally injured.…”
Section: Trends In Alcohol-related Accidentsmentioning
confidence: 99%